„Y Generation” on the contemporary labour market – dark fiction or completely new quality? - Barwińska-Małajowicz, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
A general characteristic of “Y Generation” in comparison with the other generations that are present on the global labour market of 20th/21st century was presented in the first part of the paper. In the next stage there were described the main features of the Y Generation in the context of its entering a contemporary labour market. The next part of the paper deals with some selected threats and dilemmas connected with employing the new generation of the employees.

W części początkowej niniejszego artykułu przedstawiona została ogólna charakterystyka „Generacji Y” na tle pozostałych pokoleń uczestniczących w globalnym rynku pracy na przełomie XX i XXI wieku. Następnie krótko scharakteryzowano najważniejsze cechy charakterystyczne dla „Generacji Y” w kontekście jej wejścia na współczesny rynek pracy. W dalszej części artykułu zaprezentowane zostały wybrane zagrożenia oraz dylematy związane z zatrudnianiem opisywanej w artykule nowej generacji pracowników.